Unravelling CO2 capture performance of microalgae cultivation and other technologies via comparative carbon balance analysis. Issue 6 (December 2021) - Cheng, Yoke Wang; Lim, Jeremy Sheng Ming; Chong, Chi Cheng; Lam, Man Kee; Lim, Jun Wei; Tan, Inn Shi; Foo, Henry Chee Yew; Show, Pau Loke; Lim, Steven
Abstract: Microalgae cultivation, absorption, adsorption, and membrane separation are widely applauded as promising technologies to sequester CO2 from flue gas. Herein, comparative carbon balance was used to elucidate their CO2 capture performance in the aspects of CO2 emission rates (direct, indirect, total, and net), CO2 removal efficiencies (apparent and actual), and CO2 removal rate per power input ratio. Screening criteria for effective CO2 capture system rule out energy-intensive sorption processes, put forward low energy membrane separation, and disclose alterable competency of microalgae cultivation. For CO2 capture from flue gas, microalgae ( Chlorella vulgaris ) cultivation in open raceway ponds was only inferior to membrane separation. To improve microalgal CO2 capture, the sensitivity analysis was performed by replacing original microalgae species ( C. vulgaris ) or cultivation system (open raceway pond). The microalgal CO2 capture in open raceway ponds became worse following the substitution of C. vulgaris with alternatives ( Botryococcus braunii, Chlorella kessleri, Chlorella pyrenoidosa, Scenedesmus obliquus, Spirulina sp., or Tetraselmis suecica ). For microalgal ( C. vulgaris ) CO2 capture, the competent cultivation systems included open raceway pond and airlift photobioreactor, while the bubble column, flat panel, or tubular photobioreactors were classified as non-competent systems. In short, microalgal ( C. vulgaris ) CO2 capture was technically feasible in open raceway pond or airlift photobioreactor; further, the use of airlift photobioreactor was preferred for better CO2 capture and microalgae biomass production. Due to the necessity of a huge working volume, the low scalability of microalgae cultivation could hamper the industrial application of microalgal CO2 capture from flue gas. Graphical Abstract: ga1 Highlights: Microalgal CO2 capture was benchmarked against other CO2 capture technologies. Membrane separation truly abates CO2 but high-energy sorption worsens CO2 emission. Microalgal ( C. vulgaris ) CO2 capture is just inferior to membrane separation. Substitution of C. vulgaris with other microalgae species intensifies CO2 emission. Viable microalgal CO2 capture using open raceway pond and airlift photobioreactor.